2013
DOI: 10.1186/2045-709x-21-36
|View full text |Cite
|
Sign up to set email alerts
|

Review of methods used by chiropractors to determine the site for applying manipulation

Abstract: BackgroundWith the development of increasing evidence for the use of manipulation in the management of musculoskeletal conditions, there is growing interest in identifying the appropriate indications for care. Recently, attempts have been made to develop clinical prediction rules, however the validity of these clinical prediction rules remains unclear and their impact on care delivery has yet to be established. The current study was designed to evaluate the literature on the validity and reliability of the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 174 publications
(311 reference statements)
0
93
0
1
Order By: Relevance
“…This study did not include inter-examiner or intra-examiner modules, because prior studies had reported substantial reliability for both prone and supine leg checking procedures. 1,4 Although the leg checkers were very experienced in their respective prone and supine procedures, different leg checkers using somewhat different methods may have obtained different results. The lack of agreement between prone and supine leg checking results in this study may have been attributable either to variance between the methods per se or to different impacts of the patient's body position on LLIf; the design of the study did not allow discrimination between these alternative possibilities.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study did not include inter-examiner or intra-examiner modules, because prior studies had reported substantial reliability for both prone and supine leg checking procedures. 1,4 Although the leg checkers were very experienced in their respective prone and supine procedures, different leg checkers using somewhat different methods may have obtained different results. The lack of agreement between prone and supine leg checking results in this study may have been attributable either to variance between the methods per se or to different impacts of the patient's body position on LLIf; the design of the study did not allow discrimination between these alternative possibilities.…”
Section: Limitationsmentioning
confidence: 99%
“…There are also leg checking protocols in which LLI is assessed as an evoked response, as when the head is turned or the knees flexed to 90°2 or when the examiner or patient makes contact with a part of the patient's body. 3 A review of the literature on the reliability and validity of measures used in manual therapy to localize the site of spinal manipulation 4 found varying levels of reliability for supine and prone LLI assessment procedures. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] There was also some support for the validity of measures of supine and prone LLI.…”
Section: Introductionmentioning
confidence: 99%
“…83 The diagnostic reliability of many of the indicators of somatic dysfunction is poor. [84][85][86] Palpation of tenderness has acceptable inter-examiner reliability, but reliability for palpation of segmental motion restriction or tissue texture changes is generally poor. [84][85][86] The reliability for assessment of asymmetrical bony landmarks is fair to poor, 87 unless substantial asymmetry exists.…”
Section: Diagnostic Reliability and Validitymentioning
confidence: 99%
“…[84][85][86] Palpation of tenderness has acceptable inter-examiner reliability, but reliability for palpation of segmental motion restriction or tissue texture changes is generally poor. [84][85][86] The reliability for assessment of asymmetrical bony landmarks is fair to poor, 87 unless substantial asymmetry exists. 88 Evidence suggests that consensus training can substantially improve the reliability of these findings between practitioners, 89,90 although the validity of these consensus findings still remains to be explored.…”
Section: Diagnostic Reliability and Validitymentioning
confidence: 99%
“…Students and clinicians typically master the delivery of manual therapies through a progression of lecture, laboratory sessions, and delivery to patients in clinical settings. [25][26][27][28][29][30][31][32][33][34][35] In educational settings, students often observe a teacher demonstrating a procedure, practice the technique on fellow student volunteers, and sometimes receive hands-on guidance and/or verbal feedback on their performance. [36][37][38] Researchers and educators have developed innovative bioengineering technologies, such as instrumented mannequins or treatment tables and other measurement devices, to provide objective feedback on forces, durations, and loading rates generated during SMT.…”
Section: Introductionmentioning
confidence: 99%